The Nature and Impact of Effective Strategies on Service Organizations: Case of the Saudi Telecom Company (STC) - Alshahrani, Tahani Mohammed (Journal of Economic, Administrative and Legal Sciences, 2022)
This study aimed at identify the nature of effective strategies and their impacts on service organizations by applying to the Saudi Telecom Company. The study followed the descriptive approach, and its sample consisted of (55) employees in Saudi Telecom, and it relied on the questionnaire as the main instrument. The results showed the following: 1) The study sample individuals strongly agreed on one of the effective strategies of the STCs that they take in the study of marketing, which is "the ability to accurately understand the customer’s needs. 2) The study sample individuals agreed on six of the effective strategies of the Saudi telecom companies that they used in studying marketing, the most prominent of which were: planning marketing and promotional campaigns. 3) The study sample individuals agreed on ten of the marketing strategies taken by the Saudi Telecom Company to influence the customers’ consumption decisions and their needs, the most prominent of which was the provision of Internet services in an advanced and synchronized manner. 4) The study sample individuals strongly agreed on three of the marketing strategies through modern means, the most prominent of which was that the company advertised its services through television channels and radio stations. 5) The study sample individuals agreed on two strategies of marketing through modern means at STC, the most important of which was the natural preparation of electronic catalogues for services or some devices. 6) The study sample individuals were neutral about one statement from the strategic plans axis in marketing operations at STC on studying market pricing, which was choosing a pricing policy for a limited number of clients. The study showed that there are no statistically significant differences at the level 0.05 or less in the attitudes of the study participants about (effective strategies of the Saudi Telecom Company) according to variables (age, job, qualification, and years of experience). Besides, it showed that there are no statistically significant differences at the level 0.05 or less in the attitudes of the study participants about (marketing strategies to influence the customers’ consumption decisions and needs) according to variables (age, job, and qualification). In the light of the results, the study recommended the necessity of intensifying and studying marketing strategies with a degree of accuracy and aspiration to affect customers’ consumption decisions and their needs.